Conduction Mechanism in Amorphous As2S3 (Journal of Science and Technology, 2016)
The conduction mechanism in amorphous As2S3 has been studied by investigating the variation of the electrical resistivity over the temperature range 300 – 450 K. The electrical resistivity is characterised by a mobility gap of 2.15 eV over the temperature range investigated. The dc conductivity provides evidence of conduction by excitation of charge carriers into the band  edges near the mobility edges. The results also give the possibility of conduction by a phonon-assisted hopping of polarons between localised states.